[DBN][HSO4]-Promoted facile and green synthesis of 2-Amino-4H-pyrans derivatives under microwave irradiation - Mane, Vishal; Mane, Dhanjay (Journal of Drug Delivery and Therapeutics, 2021)
The [DBN][HSO4] -promoted Knoevenagel condensation followed by cyclization protocol has been developed for the first time by a successive reaction of aldehydes, dimedone and malononitrile to afford 2-Amino-4H-pyrans derivatives in high to excellent yields at room temperature. The synergic couple of microwave and ionic liquid provided the capability to allow a variability of functional groups, short reaction times, easy workup, high yields, recyclability of the catalyst, and solvent-free conditions, thus providing economic and environmental advantages.Keywords: [DBN][HSO4], Environmentally benign, 2-Amino-4H-pyrans, Knoevenagel condensation, Microwave irradiation